2020
DOI: 10.1039/c9nj06180k
|View full text |Cite
|
Sign up to set email alerts
|

The first zwitterionic cocrystal of indomethacin with amino acid showing optimized physicochemical properties as well as accelerated absorption and slowed elimination in vivo

Abstract: The first zwitterionic cocrystal of indomethacin (INC) with proline (PL) with optimized in vitro/in vivo properties was prepared and characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…The number of hydrogen interactions may represent the solubility of the co-crystals. This phenomenon is supported by the hydrotropic effect of co-formers such as proline (PRO) to dissolve a more hydrophobic API with excellent solubility [ 23 ]. Additionally, co-crystals show increased dissolution, bioavailability, stability, and mechanical properties.…”
Section: Co-crystalmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of hydrogen interactions may represent the solubility of the co-crystals. This phenomenon is supported by the hydrotropic effect of co-formers such as proline (PRO) to dissolve a more hydrophobic API with excellent solubility [ 23 ]. Additionally, co-crystals show increased dissolution, bioavailability, stability, and mechanical properties.…”
Section: Co-crystalmentioning
confidence: 99%
“…For example, a co-crystal consisting of two APIs, namely pyrithyldione as sedative and propyphenazone as NSAID, produces three polymorphs; the polymorph form II was the most stable [ 35 ]. Since then, NSAID co-crystals have continued to develop in terms of screening, manufacturing techniques, and enhancement of physicochemical properties [ 23 , 28 , 36 , 37 , 38 ]. Furthermore, some invented NSAID co-crystals are summarized in Table 1 .…”
Section: Progress On Nsaid Co-crystalsmentioning
confidence: 99%
“…l -proline is the most soluble amino acid and can dissolve hydrophobic molecules with a hydrotropic effect. In addition, l -proline also supports the permeability properties of API, i.e., indomethacin [ 90 ]. This amino acid builds a flexible but intense interaction with another compound based on a zwitterionic interaction and a rigid structure, which added value for this co-former.…”
Section: Amino Acids As Co-formersmentioning
confidence: 99%
“…From the pharmacokinetic study, the co-crystal showed a maximum concentration that was similar to that of pure indomethacin. However, it was reached in a shorter time, and the level of the co-crystal was higher than the pure compound during the elimination process [ 90 ].…”
Section: Amino Acids As Co-formersmentioning
confidence: 99%
“…Thus, IMC shows low bioavailability and, to be effective, requires special manufacturing and increased dosage, which in turn may worsen adverse effects such as gastric irritation or renal malfunctioning. 3,8 Schemes for enhancing IMC dissolution rate and intestinal absorption include the crystallization of IMC as co-crystals, [8][9][10][11][12] salts 13 and solvates, 14,15 or its administration together with physiologic buffers or emulsions that modify the local pH. 16,17 The aqueous solubility of IMC is mainly driven by the ionization of its carboxylic group and hence it is freely soluble at pH > 4.5.…”
Section: Introductionmentioning
confidence: 99%